Agranulocytosis and secondary infection related to JAK inhibitors and IL-6 receptor blockers: a disproportionality analysis using the US Food and drug administration adverse event reporting system - Wei, Chunyan; Yin, Wanhong; Hu, Tingting; Zhang, Jingyi; Dan, Huifang; Wu, Bin (Frontiers in Pharmacology, 2024)
Background: Given that the fight against coronavirus disease 2019 (COVID-19) is not over, we aimed to explore the occurrence of agranulocytosis and infectious complications in patients with and without COVID-19 following immunoregulatory therapy based on real-world data. Methods: This was a retrospective disproportionality analysis based on the US Food and Drug Administration Adverse Event Reporting System (FAERS). All cases reported between the first quarter of 2004 and the fourth quarter of 2022 about Janus kinase inhibitors (baricitinib, tofacitinib, ruxolitinib) and interleukin-6 receptor blockers (tocilizumab, sarilumab) were collected. Disproportionality analyses were conducted by reporting odds ratio (ROR) and information component (IC). Results: A total of 211,363 cases were recognized from the FDA Adverse Event Reporting System database. Data analysis showed that tocilizumab (reporting odds ratio: 3.18, 95% CI: 3.18–3.29; information component: 1.37, 95% CI: 1.31–1.42), sarilumab (ROR: 1.64, 95% CI: 1.55–1.73; IC: 0.61, 95% CI: 0.43–0.79), baricitinib (ROR: 3.42, 95% CI: 3.19–3.67; IC: 1.43, 95% CI: 1.21–1.65), tofacitinib (ROR: 2.53, 95% CI: 2.49–2.57; IC: 1.11, 95% CI: 1.05–1.16), and ruxolitinib (ROR: 1.87, 95% CI: 1.83–1.91; IC: 0.77, 95% CI: 0.70–0.84) were all associated with secondary infection. The association in the combination group was higher than that in the monotherapy group (ROR: 4.69, 95% CI: 4.53–4.86; IC: 1.73, 95% CI: 1.62–1.84). As for agranulocytosis, tocilizumab (ROR: 1.61, 95% CI: 1.53–1.69; IC: 0.67, 95% CI: 0.50–0.84) and ruxolitinib (ROR: 2.32, 95% CI: 2.21–2.43; IC: 1.18, 95% CI: 1.02–1.33) showed the significant signals. The association was higher in the combination group than in the monotherapy group (ROR: 2.36, 95% CI: 2.15–2.58; IC: 1.20, 95% CI: 0.90–1.51). Secondary infection after treatment with tofacitinib (ROR: 1.37, 95% CI: 1.02–1.84), tocilizumab (ROR: 1.46, 95% CI: 1.01–2.09), and sarilumab (ROR: 2.46, 95% CI: 1.10–5.50) was reported more frequently in COVID-19 than in non–COVID-19 patients. Conclusion: Both Janus kinase inhibitors and interleukin-6 receptor blockers are significantly associated with secondary infection and agranulocytosis, and the combined treatment further increases the association. The correlation with secondary infection in patients treated with tofacitinib, tocilizumab, and sarilumab is higher in COVID-19 than in non–COVID-19 patients.